Baseline Characteristics of a Dyadic Cohort of Mothers With Chronic Pain and Their Children. Issue 10 (October 2020) - Wilson, Anna C.; Stone, Amanda L.; Poppert Cordts, Katrina M.; Holley, Amy L.; Mackey, Sean; Darnall, Beth D.; Palermo, Tonya M.
Abstract : Objectives: A growing body of research has demonstrated a robust link between parental chronic pain and child pain and psychological function. Although the association between parent and child pain is strong, there are limited data to understand environmental and behavioral processes that account for the association and how this develops over time. This longitudinal cohort study was designed to understand the potential mechanisms that confer risk or resilience for chronic pain among child offspring of mothers with chronic pain. Methods: The current paper presents baseline data on the cohort to describe the pain and psychosocial characteristics of mothers with chronic pain and their 8- to 12-year-old children. A total of 400 mothers with chronic pain and their children were enrolled into the longitudinal study and completed measures of pain, physical, and psychosocial functioning. Results: Mothers reported a range of pain and pain-related disability and were grouped into 4 pain grades (PGs) representing different pain and disability levels. Mothers in these groups differed on rates of widespread pain and opioid use. Maternal PGs also differed by physical function, fatigue, sleep disturbance, and psychological function. Most children in this sample reported pain and psychosocial symptoms in the nonclinical range, and child variables did not differ by maternal PG. Maternal disability and function were concurrently associated with child psychosocial function. Discussion: While maternal PGs map broadly onto several dimensions of maternal functioning, they were not significantly related to child pain or function. Results may help identify potential protective factors in the intergenerational transmission of risk for chronic pain.